Central Activating Transcription Factor 4 (ATF4) Regulates Hepatic Insulin Resistance in Mice via S6K1 Signaling and the Vagus Nerve - Zhang, Qian (American Diabetes Association, 2013)
Recent studies have revealed that the central nervous system, particularly the hypothalamus, is critical for regulating insulin sensitivity in peripheral tissues. The aim of our current study is to investigate the possible involvement of hypothalamic activating transcription factor 4 (ATF4) in the regulation of insulin sensitivity in the liver. Here, we show that overexpression of ATF4 in the hypothalamus resulting from intracerebroventricular injection of adenovirus expressing ATF4 induces hepatic insulin resistance in mice and that inhibition of hypothalamic ATF4 by intracerebroventricular adenovirus expressing a dominant-negative ATF4 variant has the opposite effect. We also show that hypothalamic ATF4-induced insulin resistance is significantly blocked by selective hepatic vagotomy or by inhibiting activity of the mammalian target of rapamycin (mTOR) downstream target S6K1. Finally, we show that inhibition of hypothalamic ATF4 reverses hepatic insulin resistance induced by acute brain endoplasmic reticulum (ER) stress. Taken together, our study describes a novel central pathway regulating hepatic insulin sensitivity that is mediated by hypothalamic ATF4/mTOR/S6K1 signaling and the vagus nerve and demonstrates an important role for hypothalamic ATF4 in brain ER stress–induced hepatic insulin resistance. These results may lead to the identification of novel therapeutic targets for treating insulin resistance and associated metabolic diseases.